Opening up education for inclusivity across digital economies and societies - Ordóñez de Pablos, Patricia 1975- (IGI Global, 2019)
"This book explores initiatives, policies and cases to support technology-use and digital competence development in education systems around the world. It discusses experiences and challenges at all levels, from academic staff and administrators, to researchers and designers; from institutions to open, distance and lifelong learning"--
Keywords: Distance education; Open learning; MOOCs (Web-based instruction); Internet in higher education; Educational technology